2010
DOI: 10.1007/s00595-009-4108-4
|View full text |Cite
|
Sign up to set email alerts
|

Is minimally invasive surgery appropriate for small differentiated thyroid carcinomas?

Abstract: Purpose. To retrospectively evaluate the surgical completeness of minimally invasive total thyroidectomy for small (<20 mm) differentiated thyroid carcinoma (DTC). Methods. The subjects of this study were 30 patients who underwent minimally invasive total thyroidectomy as a single procedure. We registered the following postoperative measurements in the LT4 withdrawal period: serum thyroglobulin level, 6-h radioiodine uptake diagnostic test results, and neck ultrasound (US) fi ndings. Results. The mean serum th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…Although scars in exposed regions of the body such as the neck are of major concern to patients, conventional open thyroidectomy, with or without LnD, has been shown to be safe and effective in managing thyroid disease [10][11][12]. Surgeons or patients may choose conventional thyroid surgery after considering disease status and the increased time and cost required for minimally invasive procedures [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Although scars in exposed regions of the body such as the neck are of major concern to patients, conventional open thyroidectomy, with or without LnD, has been shown to be safe and effective in managing thyroid disease [10][11][12]. Surgeons or patients may choose conventional thyroid surgery after considering disease status and the increased time and cost required for minimally invasive procedures [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The safest indication for MIVAT has been reported by a recent review to be benign disease [7]. However, in contrast, another recent review article found minimally invasive thyroidectomy or endoscopic techniques to be oncologically acceptable in 92 patients with low or intermediate risk thyroid cancer (including two patients with medullary cancer) [8], and a series of 30 patients found minimally invasive thyroidectomy to be an appropriate approach in small diVerentiated thyroid cancers [9]. A further review by Miccoli et al [10] found that MIVAT is indicated for papillary cancers and has the same oncologic outcome as conventional surgery, but should not be used for locally invasive disease or medullary or anaplastic carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…Ruggieri et al recommended minimally invasive total thyroidectomy for small PTC, because its short-term outcome did not differ from conventional surgery. 1 However, lymph node dissection is actively recommended only for patients with metastasis detectable on preoperative imaging studies in Western countries. The indications for prophylactic CND are limited, and prophylactic MND is not recommended in Western guidelines.…”
Section: Introductionmentioning
confidence: 99%